Adjusting scheduling model with release and due dates in production planning. Issue 1 (1st January 2017) - Chinos, Elisa; Vakhania, Nodari
Abstract : Motivated by the conjecture that an interaction between scheduling and pre-scheduling phases in production planning may give certain benefits, we conduct a detailed study of the optimality conditions and dominance relations for a strongly NP-hard single-machine scheduling model when jobs have release and due-dates and the objective is to minimize maximum job lateness. By exploring the inherent structure of the problem, we establish the optimality conditions when the problem can be efficiently solved. We come to an NP-hard special case of the problem with only two possible job release times, that as we show allows stricter dominance rules and optimality conditions verifiable in polynomial time. The established properties give a potential of a beneficial interaction between scheduling and pre-scheduling phases in production planning, and also provide basic theoretical background for the construction of efficient heuristic and implicit enumerative algorithms.